2018
DOI: 10.1111/iwj.12984
|View full text |Cite
|
Sign up to set email alerts
|

Specific foot health‐related quality‐of‐life impairment in patients with type II versus type I diabetes

Abstract: The aims of this research were to evaluate and compare the effect in a matched sample of patients with type II and type I diabetes scores using a specific quality-of-life (QoL) tool related to overall and foot health (Foot Health Status Questionnaire [FHSQ]). A sample of 62 patients with an age median of 59.00 ± 19.00 y were divided into type I (n = 31) and type II (n = 31) diabetes groups. Socio-demographics data include: (1) age, (2) gender, (3) body mass index, (4) professional activity, (5) study level, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…Vozarova et al compared cardiovascular diseases and diabetes in the Roma and non-Roma population reporting a high prevalence in Roma population [42], in line with Ramos-Morcillo et al [39]. Furthermore, Palomo-López et al reported that foot problems, including those arising from chronic diseases such as diabetes, can provoke limitations, deformities and disabilities [24]. The prevalence of foot health problems was higher in Roma women than in Roma men and such disorders can be prevented or minimized, among other measures, by adopting a healthy lifestyle "healthy behaviour" and by entrusting foot care to qualified specialists.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Vozarova et al compared cardiovascular diseases and diabetes in the Roma and non-Roma population reporting a high prevalence in Roma population [42], in line with Ramos-Morcillo et al [39]. Furthermore, Palomo-López et al reported that foot problems, including those arising from chronic diseases such as diabetes, can provoke limitations, deformities and disabilities [24]. The prevalence of foot health problems was higher in Roma women than in Roma men and such disorders can be prevented or minimized, among other measures, by adopting a healthy lifestyle "healthy behaviour" and by entrusting foot care to qualified specialists.…”
Section: Discussionmentioning
confidence: 80%
“…This is an under-researched population, and as such the work is of interest. National health surveys of the Roma population in Spain and Europe have been carried out within the framework of the European project entitled "Health and the Roma community, analysis of the situation in Europe" [9] [36], which has been adapted and translated to know foot health in certain pathologies [18] [23] [24], and on populations with certain characteristics [19] [20] [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the variables included in the model, we observed that “low educational level” increases the risk of losing protective sensitivity (OR: 31.4, 95% CI: 2.5‐383.3, P = .007); however, the confidence interval is quite high, so the risk—although present—may be overestimated by the sample size. Those with a lower level of education typically have poorer health habits, causing increased obesity, physical inactivity, and susceptibility to psychosocial risks, which increases the risk of suffering from neuropathy . Therefore, it is important to establish preventative programs aimed at less educated populations to reduce the prevalence of PN.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the need for surgeons to attempt foot salvage procedures before performing a major amputation [7]. In 2019 Palomo-Lopez et al evaluated 62 patients by means of Foot Health Status Questionnaire and pointed out that the patients with type II diabetes present a negative impact on the speci c foot health-related QoL compared with type I diabetes patients [8]. In 2017 López-López et al studied the foot health-related beliefs of 282 patients and con rmed the positive social attitude to podiatry, which help the patients to lead a healthy life and avoid dependency [9].…”
Section: Introductionmentioning
confidence: 95%